2011
DOI: 10.1016/j.limno.2010.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive traits of the freshwater shrimp Caridina fossarum Heller, 1862 (Decapoda, Caridea, Atyidae) in the Ghomp-Atashkedeh spring (Iran)

Abstract: a b s t r a c tIn the present study, some biological traits of Caridina fossarum reproduction are studied in the GhompAtashkedeh spring (Fasa, Shiraz, Iran), for the first time. This Iranian endemic freshwater species was studied from April 2007 to March 2008. Minimum sexable size (MSS) and absolute or relative size at the onset of maturity (SOM and RSOM) in terms of carapace length (CL) was found to be 2.4 mm, 4.3 mm and 55%, respectively. Sex ratio showed variations on a monthly basis. Sex reversal is a poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
0
11
1
Order By: Relevance
“…Fecundity increases with body size in M. acanthurus as reported before for most species of caridean shrimps, including members from the genus Macrobrachium, in which fecundity has been studied (Macrobrachium: Ching & Velez 1985;Graziani et al 1993;Anger & Moreira 1998;Da Silva et al 2004;Wehrtmann & Lara 2009;Tamburus et al 2012;other genera: Corey & Reid 1991;Lardies & Wehrtmann 1997;Anger & Moreira 1998;Ramirez-Llodra et al 2000;Ramirez-Llodra 2002;Oh et al 2003;Penha-Lopes et al 2007;Zare et al 2011 (Table 1). Overall, M. acanthurus exhibits an average fecundity that represents one of the extremes regarding the trade-off between fecundity and egg-size reported for caridean shrimps and other decapod crustaceans (Sastry 1983;.…”
Section: Discussionmentioning
confidence: 57%
“…Fecundity increases with body size in M. acanthurus as reported before for most species of caridean shrimps, including members from the genus Macrobrachium, in which fecundity has been studied (Macrobrachium: Ching & Velez 1985;Graziani et al 1993;Anger & Moreira 1998;Da Silva et al 2004;Wehrtmann & Lara 2009;Tamburus et al 2012;other genera: Corey & Reid 1991;Lardies & Wehrtmann 1997;Anger & Moreira 1998;Ramirez-Llodra et al 2000;Ramirez-Llodra 2002;Oh et al 2003;Penha-Lopes et al 2007;Zare et al 2011 (Table 1). Overall, M. acanthurus exhibits an average fecundity that represents one of the extremes regarding the trade-off between fecundity and egg-size reported for caridean shrimps and other decapod crustaceans (Sastry 1983;.…”
Section: Discussionmentioning
confidence: 57%
“…Fecundity, defined as the number of offspring produced by a female in a determined time period, is directly related to energy allocation and is essential in estimating reproductive potential of a population (Ramirez-Llodra 2002, Zare et al 2011). Embryo size is an indicator of the energy allocation, duration of embryogenesis and type of larval development (Dardeau 1984, Ramirez-Llodra 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Intra-specific variations in body size, brood size and number of eggs among local populations, as well as two reproductively isolated populations in a single river basin, have been reported for R paucidens in Japan (Nishino, 1980;Chow et al, 1988), other palaemonids (Omori & Chida, 1988;Collart & Rabelo, 1996;Bilgin & Samsun, 2006;Janas & Mañkucka, 2010) and other carideans (Oh & Hartnoll, 1999;Zare et al, 2011). i…”
Section: Breeding Periodmentioning
confidence: 98%
“…Matocec et al, 2006); it has been suggested that the relative abundance of females during the breeding period in P. paucidens populations is a reproductive strategy to increase the number of recruits via reproduction, as observed in other freshwater shrimps, such as Caridina fossarum Heller, 1862 (cf. Zare et al, 2011), and Macrobrachium iheringi Ortmann, 1897 (cf. Fransozo et al, 2004).…”
Section: Sex Ratiosmentioning
confidence: 99%
See 1 more Smart Citation